Digital Transformation Trends and Innovation. Issue 1 (March 2021) - Guarda, Teresa; Balseca, Joel; García, Kevin; González, Jairon; Yagual, Fabian; Castillo-Beltran, Hernán
Abstract: Today, advances in technology bring changes to people's lifestyles, and challenging organizations to accompany these advances. Organizational managers and those responsible for the Information Technology (IT) department must evaluate current trends in innovation, and determine how they can boost business, creating new business models, and promoting competitiveness. The objective of these paper is presented a group of technological advances aimed at being the latest digital trends and changing previous trends by producing improvements or updates, the same ones that streamline processes in the field of business intelligence (BI). In this survey paper, current trends in the Internet of Things (IoT) are described, as well as topics related to 5G mobile communication, WiFi 6 technologies, the transformation of the user's technological experience, and Machine Learning (ML). In addition, the support in decision-making process will be analysed as these trends, both personally and at the business level.